2007
DOI: 10.1002/elps.200700171
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated ethylenepropylene copolymer as a potential capillary material in CE

Abstract: In this work, a new generation UV-transparent polymer, fluorinated ethylenepropylene copolymer (FEP) exhibiting a low degree of crystallinity, extruded in dimensions similar to the most commonly used CE capillaries of approximately 80 mum id and about 360 mum od was investigated for its use as a CE capillary. FEP is transparent down to the low-UV region, and as fluorinated polymers in general are good electrical insulators and exhibit reasonable heat conductivity, it has considerable potential as a material fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…3). As previously reported in other studies employing fluorinated materials, 16,17 a cathodic EOF is observed highlighting the negative charge of the Dyneon THV surface. At pH 7.4, µ EO of Dyneon THV is 28.3 ± 0.2 × 10 −5 cm 2 V −1 s −1 which is similar to the COC 24 values (26.6 ± 0.1 × 10 −5 cm 2 V −1 s −1 ) at the same pH.…”
Section: Electroosmotic Mobilitysupporting
confidence: 85%
See 1 more Smart Citation
“…3). As previously reported in other studies employing fluorinated materials, 16,17 a cathodic EOF is observed highlighting the negative charge of the Dyneon THV surface. At pH 7.4, µ EO of Dyneon THV is 28.3 ± 0.2 × 10 −5 cm 2 V −1 s −1 which is similar to the COC 24 values (26.6 ± 0.1 × 10 −5 cm 2 V −1 s −1 ) at the same pH.…”
Section: Electroosmotic Mobilitysupporting
confidence: 85%
“…15,16 For instance, the simultaneous separation of nine cations and anions on an unmodified fluorinated ethylenepropylene (FEP) capillary has been successfully obtained. 17 Sahlin et al 18 also showed that an in-house made fluorinated capillary allowed a more efficient separation of two cationic aromatic molecules than a fused silica (FS) capillary. Tsukagoshi et al 19 obtained a better resolution of isoluminol isothiocyanate (ILITC) and hydrolyzed ILITC in a polytetrafluoroethylene capillary as compared to a FS capillary which generated a higher electroosmotic flow (EOF).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorinate ethylenepropylene copolymers have been tested in ion analysis as a new material for capillary production both with direct and indirect LED detection. Indeed, fluorinate ethylenepropylene presents relevant advantages in terms of transparency in the low‐UV‐region though maintaining a reasonable heat conductivity, making it attractive for electrodriven separations 35.…”
Section: Small Ions Of Forensic Interestmentioning
confidence: 99%
“…For certain applications, e.g . where hydrophilic wall interactions typical to fused‐silica capillaries are problematic, a capillary made of a fluorinated ethylenepropylene copolymer 101 may provide higher efficiencies. However, modest mechanical stability and light scattering at λ≤214 nm, resulting in the baseline noise, are obstacles to its implementation for routine use.…”
Section: Separation Systems: Incremental Progressmentioning
confidence: 99%
“…6 provided tenfold lower LODs and faster separations. The benefits of a movable LED detector have been amply demonstrated by the same group when optimizing the selectivity in simultaneous separation of anions and cations 101. Additionally, a range of compounds were evaluated as probes for the indirect detection of inorganic anions using LEDs as the light source, with the aim to replace the very effective but toxic chromate 122.…”
Section: Detection: Further Instrumental Developmentsmentioning
confidence: 99%